Ovarian hyperstimulation syndrome. A case report - Práxedes de Regla Rojas Quintana; Sandra Gómez Fonseca; Alejandrina Najarro Navarro (Medisur)
Ovarian hyperstimulation syndrome is an exaggerated response to excess hormones. For years, this condition has questioned the actions of physicians due to its complex pathophysiology and devastating consequences for patients of reproductive age. For these reasons, the case of a patient who underwent medical and surgical treatment, with in vitro fertilization and embryo transfer, who developed severe ovarian hyperstimulation syndrome with pregnancy si presente Since the syndrome could not be controlled and worsened with pregnancy and sepsis, with changes in addition to hepatorenal dysfunction, it was decided to terminate the pregnancy at six weeks of gestation, since the patient's life was in danger, and antibiotic therapy was started for sepsis. After 25 days of hospitalization, she was discharged from the institution after recovery and was followed up by assisted reproduction consultation. After a year without any procedure, in vitro fertilization was performed again for her complete recovery; a clinical pregnancy was achieved, with favorable evolution and normal birth.